Taras Shevchenko in foreign media: lingvoimage discourse - Pliasun , Olga (Current issues of Ukrainian linguistics: theory and practice, 2021)
The article considers the linguistic specifics of modeling the image of Taras Shevchenko in foreign media. The author's attention is focused on the great image-forming potential of this iconic, precedent for Ukrainian culture personality and the importance of its correct presentation in the modern media space. It is determined that Ukrainians themselves are the main creators of image texts about Kobzar in the world media. Thus, three main channels of image information about Shevchenko abroad are analyzed: (1) cultural diplomacy as a part of the "soft power" policy; (2) the Ukrainian diaspora, which addresses the figure of Kobzar in the media; (3) information resources of world encyclopedic publications dedicated to the poet. Thus, the study of the linguistic and image specifics of the representation of Shevchenko in the foreign media proves that a great deal of image-making work in this aspect is carried out by cultural diplomacy, which represents Ukraine and its national cultural products in the world information space. Thanks to the efforts of cultural diplomacy, Shevchenko is known and appreciated abroad, as evidenced by the activities of Ukrainian embassies. In the context of linguistic imageology, the information presented by Ukrainian embassies is unambiguously of image nature, which confirms the use of effective linguistic means of image modeling: metaphors, personifications, emotionally-evaluative lexemes, epithet forms of the word, which verbalize positive author's assessment of the covered information. An equally important linguistic tool for modeling the poet's image is the use of creolized media texts that have great suggestive properties and significant image potential. In addition, Shevchenko's positive image abroad is successfully constructed by the media resources of the Ukrainian diaspora. The author's attention in this research context is attracted by the leading Canadian and Australian media. From the standpoint of linguistic imageology, effective means of forming the image of Kobzar in the considered foreign media are emotional and evaluative lexemes with elements of hyperbole, paraphrase with a positive semantics, the use of oxymoron etc. The article emphasizes that Shevchenko's positive image abroad is created not only at the textual level, but also at the extralinguistic level, which is realized in the annual holding of numerous mass events related to the celebration of Shevchenko's days. In turn, a high assessment of the poet's work and his role in Ukrainian cultural life is found in world encyclopedic publications: Encyclopædia Britannica, Oxford World Encyclopedia, bibliographic fund of The Library of Congress etc. Thus, the study convinces that Taras Shevchenko is a bright image figure of modern foreign media space, which forms not only internal but also external image of Ukraine. That is why its correct presentation in world media should be one of the priorities of the national image strategy.
Keywords: linguistic imageology, media image, linguistic means of image modeling, image text, Taras Shevchenko.